Community nurses’ willingness to implement Advance Care Planning (ACP) and their attitudes toward death: current status and correlation analysis - Peng, Qiyan; Dong, Yujie; Dai, Qin; Zhang, Chi; Li, Xiaoling (Frontiers in Medicine, 2025)
ObjectiveThis study aims to evaluate the current status of community nurses’ willingness to implement Advance Care Planning (ACP) and their attitudes toward death, and to explore the correlation between these variables, providing a basis for improving ACP implementation strategies.MethodsA convenience sampling method was employed to select 317 nurses from 15 community health service centers in Chengdu. Data were collected using a general information questionnaire, the ACP Implementation Willingness Scale, and the Death Attitude Profile-Revised (DAP-R).ResultsThe overall score for community nurses’ willingness to implement ACP was 56.87 ± 9.73, indicating a moderately high level of willingness. In terms of death attitudes, the highest score was observed in the “natural acceptance” dimension (3.76 ± 0.63), followed by “death avoidance” (3.20 ± 0.81) and “death fear” (3.07 ± 0.80). A significant negative correlation was found between ACP implementation willingness and both “death fear” and “death avoidance” (r = −0.358 to −0.414, P < 0.001). In contrast, a positive correlation was observed between ACP implementation willingness and “natural acceptance,” “approach acceptance,” and “escape acceptance” (r = 0.151 to 0.494, P < 0.001). Multiple stepwise linear regression analysis revealed that age, education level, previous exposure to death education training, familiarity with or exposure to ACP, and death attitudes (particularly “death avoidance” and “natural acceptance”) were the main factors influencing nurses’ willingness to implement ACP, explaining 40.4% of the total variance.ConclusionCommunity nurses’ willingness to implement ACP is moderately high; however, their understanding of ACP remains limited. Death attitudes are primarily characterized by “natural acceptance,” though negative attitudes toward death, such as “death avoidance,” persist. Enhancing death education and training, improving nurses’ understanding of ACP, and fostering a more accurate perception of death are essential to facilitate broader ACP implementation in the general population.